Perceptions of the safety, development, and approval process of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines among individuals with Affordable Care Act health insurance in Central Texas at the time of initial vaccine availability - Carlos Lopez Bray; Richard Taylor; Naomi Tamez; Wesley Durkalski; John R. Litaker (Frontiers in Public Health)
Sendero Health Plans, an Affordable Care Act (ACA) health insurance company, conducted a cross-sectional survey in December 2020 to assess individual perceptions of the COVID-19 vaccine development and approval processes and their plan to obtain the COVID-19 vaccine in Central Texas at the time of initial availability. A logistic regression model was developed to identify factors associated with individual plans to obtain a vaccine when it became available. A total of 500 (77.25%) of the 645 respondents in this analysis planned to obtain a COVID-19 vaccine when it became available. The logistic regression model was statistically significant [χ2(19) = 314.41, p < 0.001]. Plans to obtain a COVID-19 vaccine were significantly associated with perceptions of vaccine safety (POR: 23.45, p = 0.001, 95% CI: 3.10, 58.34), vaccine protectiveness (POR: 15.55, p < 0.001, 95% CI: 3.55, 68.06), and transparency of the authorization process (POR: 1.33, p = 0.024, 95% CI: 1.15, 7.15). Perceptions regarding the safety, protectiveness, and authorization process of the COVID-19 vaccines are associated with individual plans to obtain the vaccines. This study provides insights into factors that influence vaccination intent and key barriers affecting vaccine hesitancy during a public health crisis.